Macroeconomic Impact Analysis of Kusile and Medupi Electricity Generation Investment: An Eye Bird View at Construction and Operational Phase (Global Journal of Management and Business Research, 2019)
Economic growth, unemployment, and inequality have been challenges facing South Africa in the past decade. Amongst others, energy security is one of the underlying factors of declining foreign direct investment and economic growth. This study investigates the impact of electricity investment in Kusile and Medupi power plant on the macroeconomic environment of South Africa with the application of the Social Accounting Matrix Model (SAM). The study results show that the infrastructure investment in the two-power station has a positive impact in the South African Economy at the macroeconomic level. Furthermore, infrastructure investment shows to have a positive impact on GDP and does add significant value to Gross Fixed Capital Formation in the country at both construction and operational phase of Kusile and Medupi. Furthermore, household income is positively impacted by the economy as a result of electricity infrastructure investment. The SAM-based Model shows that total employment will be positively impacted and labor force with different skills level will unequally benefit.
Keywords: economic growth; macroeconomic; employment; electricity; infrastructure